Promotion of Social Entrepreneurship Through Public Services in the Madrid Region: Succesful Aspects - M. Teresa Fernández Fernández; Ana Fernández-Ardavín Martínez; David Berenguer Herrero (Amfiteatru Economic Journal, 2012)
This article analyzes the promotion of social entrepreneurship through the delivery of services in public business incubators in the Madrid region. The research is innovative since the implication of the public sector in boosting social entrepreneurship is quite new in Spain. Methodology starts with a literature revision of the factors conforming social entrepreneurship and focuses on networking. Then, social entrepreneurship presence and its promotion is analyzed both in the practices and services provided by the Madrid Development Agency in its “Madrid Emprende” incubation program and also through a survey addressed to the 113 firms hosted in its network of business incubators. Results of the survey show that social entrepreneurship is present as the main purpose of their activity in a majority of the firms, in their social products and services, in their social legal form supported by the public network and in some forms of public-private partnership promoted by the Madrid Business Incubators Network. Services provided by the public network show the quality, the added value and the know-how of the practices of the public program and have an impact in the efficient performance of the firms regarding social entrepreneurship and in the public-private alliances established for some social purposes.
Keywords: L26; H4; L84; 330; social entrepreneurship; service innovation; public-private networks